Parameterized Gregory Formula - Khelil, N.; Djerou, L. (Communications in Mathematics and Applications, 2017)
In this article we prove that the Gregory Formula \((G)\) can be optimized by minimizing some of their coefficients in the remainder term. Experimental tests prove that obtained Formula can be rendered a powerful formula for library use.